Design of Composite Stanchions for the Cargo Subfloor Structure of a Civil Aircraft. (2016) - Di Caprio, F.; Ignarra, M.; Marulo, F.; Guida, M.; Lamboglia, A.; Gambino, B.
Abstract: The present work was performed in the frame of a national research program focused on the development of analysis method able to improve the structural response of civil aircraft subject to crash event. In particular, the aim of the program is to demonstrate the energy absorption capability of the lower lobe section of the fuselage aircraft. One of principal substructures, which is able to absorb the impact energy in a crash event, is the cargo subfloor. In this work, the results obtained by an experimental test campaign on cargo subfloor elements are presented. The test case consists in a full scale composite stanchion. The experimental results were used to provide information useful to set the numerical models. Indeed, setting and calibrating the numerical models is an important point in order to have useful tools able to improve the absorption energy capability by means of optimization analyses. The stanchion was tested under static and dynamic load conditions, at different impact energy levels.